2012
DOI: 10.1590/s0102-695x2012005000047
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of oil from the seed of Carapa guianensis (andiroba) in the control of Felicola subrostratus

Abstract: This study was perfomed to assess the in vitro effect of oil from the seed of andiroba (Carapa guianensis Aubl.) on Felicola subrostratus (Burmeister, 1838) (Mallophaga: Trichodectidae). Six hundred specimens of F. subrostratus from neighborhood of Jordão, Recife-PE, Brazil, were collected by hand directly from the fur of cats infested naturally. The lice were transported in plastic recipients to the Laboratory of Parasitic Diseases of Domesticated Animals of the Department of Veterinary Medicine of the Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
2
8
0
1
Order By: Relevance
“…The concentration of 1000 mg/ml caused 94% mortality of the lice, 1 h post-exposure. These results are similar to those found by Barros et al (2012) and Farias et al (2017), when testing the same oil on chewing lice at 100% concentration, observed total mortality of Felicola subrostratus and Damalinia caprae, respectively, after starting the evaluation.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The concentration of 1000 mg/ml caused 94% mortality of the lice, 1 h post-exposure. These results are similar to those found by Barros et al (2012) and Farias et al (2017), when testing the same oil on chewing lice at 100% concentration, observed total mortality of Felicola subrostratus and Damalinia caprae, respectively, after starting the evaluation.…”
Section: Resultssupporting
confidence: 90%
“…Similar results were obtained by Farias et al (2017), who, when using high concentrations of andiroba oil and monosulfiram (positive control), obtained 100% efficacy. Barros et al (2012) obtained similar results when working with lice specimens (F. subrostratus).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Hammer & Johns (1993), Hammer & Johns (1993), Pessoa (2009), Ritter et al (2012), Monteiro et al (2011), Pessoa (2009), Oliveira et al (2003), Ritter et al (2012), Monteiro et al (2011), Pessoa (2009), Silva et al (2004), Prophiro et al (2012), Silva et al (2004), Prophiro et al (2012), Silva et al (2004), Prophiro et al (2012), Silva et al (2004), Prophiro et al (2012), Silva et al (2004), Prophiro et al (2012), Santos et al (2012), Ambrozin et al (2006); Silva et al (2009), Silva et al (2012), Mirada Júnior et al (2012), , Penido et al (2006), Penido et al (2005), Hammer & Johns (1993, Tappin et al (2008), , Sehorini (2010), Costa- ), Hammer & Johns (1993, Tappin et al (2008), , Sehorini (2010), Costa- ), D'Alessandro (2009, Nayaki et al 2010, Menezes (2008), Penido et al (2006), Penido et al (2005), Andrade et al (2001), Barros et al (2012), Barros (2011), Andrade (2008), Farias et al (2010), , , Penido et al (2006), Penido et al (20...…”
Section: Seed Seedmentioning
confidence: 99%
“…O óleo misturado com cinzas e casca de cacau é utilizado como repelente e inseticida (FERRARI et al, 2007;SANTOS et al, 2014;KLAUCK et al, 2015;NARDI et al, 2016;PARREIRA et al, 2018). O óleo ainda é usado contra carrapatos, pulgas, larvas, piolhos, sarnas e picadas de insetos (BARROS et al, 2012;BARROS et al, 2015;ROMA et., 2015;JESUS et al, 2017). O fruto é usado por alguns insetos como meio de oviposição e nutrição das larvas até a forma adulta.…”
Section: Introductionunclassified